Peran Talent Management dan Employee Experience dalam Meningkatkan Loyalitas Karyawan di Industri E-Commerce - Januar Ida Wibowati; Yuli Alam; Hendriansyah Hendriansyah; Dora Indah Triana; Maiza Fikri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the role of talent management and employee experience in enhancing employee loyalty in the e-commerce industry through a non-empirical, conceptual approach. The study employs a qualitative design with a mixed-methods literature synthesis to construct a model of the relationship between talent management, work experience, and digital workforce loyalty. Data were obtained through a review of reputable international and national scientific literature addressing talent management, employee experience, employee engagement, retention, and employee loyalty in the digital and e-commerce sectors from 2020 to 2026. Analysis was conducted using thematic synthesis and comparative conceptual analysis, with the high turnover rate in the e-commerce industry serving as the primary interpretive context. The research findings indicate that employee loyalty is fostered through the integration of competency development, career development, rewards and recognition, employer branding, work flexibility, organizational communication, and psychological safety. Employee experience strengthens employee engagement and organizational commitment, while talent management enhances perceptions of organizational support and professional career sustainability. The study’s conceptual model demonstrates that the integration of these two variables contributes to workforce retention, organizational stability, productivity, and the enhancement of e-commerce companies’ competitiveness in a competitive digital business environment